1995
DOI: 10.1128/aac.39.9.2023
|View full text |Cite
|
Sign up to set email alerts
|

Clinically achievable plasma deferoxamine concentrations are therapeutic in a rat model of Pneumocystis carinii pneumonia

Abstract: The iron-chelating drug deferoxamine (DFO) has been shown to be active in animal models of Pneumocystis carinii pneumonia (PCP), with effective daily intraperitoneal bolus dosages being 400 and 1,000 mg of DFO mesylate kg of body weight ؊1 in mouse and rat models, respectively. Continuous infusion produced a moderately improved response in a rat model. The data reported here demonstrate that the response achieved by continuous infusion of 195 and 335 mg of DFO mesylate kg ؊1 day ؊1 in the rat model is associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Inclusion of this nutrient was suggested by previous work showing stimulation of nucleic acid and protein biosynthesis in Saccharomyces cerevisae culture as well as outgrowth of ascospores (17). Because we found that the strong iron chelator deferoxamine is an active anti-PCP agent in an animal model (16,(18)(19)(20), we added the soluble, relatively weak chelate ferric pyrophosphate to provide an available source of iron, as was done for Legionella pneumophila culture (21). The requirement for P. carinii to be attached to a surface has been noted many times but always with reference to a host cell or, in culture, a mammalian cell feeder layer (22)(23)(24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 99%
“…Inclusion of this nutrient was suggested by previous work showing stimulation of nucleic acid and protein biosynthesis in Saccharomyces cerevisae culture as well as outgrowth of ascospores (17). Because we found that the strong iron chelator deferoxamine is an active anti-PCP agent in an animal model (16,(18)(19)(20), we added the soluble, relatively weak chelate ferric pyrophosphate to provide an available source of iron, as was done for Legionella pneumophila culture (21). The requirement for P. carinii to be attached to a surface has been noted many times but always with reference to a host cell or, in culture, a mammalian cell feeder layer (22)(23)(24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 99%
“…Most in vitro experiments used P. carinii cells freshly isolated from infected rat lungs. To induce PCP, rats were pretreated with antibiotics to suppress other infections, immunosuppressed by adding dexamethasone to the drinking water, and inoculated by intratracheal instillation of a homogenate of a P. carinii-infected rat lung as previously described (14). After the development of pneumonia, the rats were sacrificed and the lungs were removed.…”
Section: Methodsmentioning
confidence: 99%
“…Tissue collection and processing as well as highpressure liquid chromatography (HPLC) analysis of DFO were performed as previously reported (15). Briefly summarized, this involved collection and homogenization of tissues, addition of ferric chloride to the homogenate to convert DFO to feroxamine (FO, the relatively stable DFO-ferric ion conjugate), and partial purification of FO by solid-phase extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Although there are several drugs and drug combinations available for PCP, all have shortcomings of toxicity, lack of efficacy, or both (30), so that introduction of a new highly effective and well-tolerated anti-P. carinii agent would be a welcome development. We and others previously reported that the iron chelator deferoxamine (DFO), currently used to treat iron overload, is active in animal models of PCP (3,15,16,29). Significantly, the plasma DFO concentration effective in a rat model of PCP is only one-third of that for ␤-thalassemia patients administered a daily, lifelong DFO dosage to reduce the iron overload resulting from the transfusions required to treat this disease (15).…”
mentioning
confidence: 99%